Effect of Marinating on Selected Quality Characteristics of Pork Tenderloin Cooked by Sous Vide Method - Marian Gil; Mariusz Rudy; Paulina Duma-Kocan; Renata Stanisławczyk; Aleksandra Wolińska; Anna Krajewska; Dariusz Dziki (Foods)
The aim of this study was to evaluate the effect of marinade type and marinating time on the physicochemical and sensory properties of pork tenderloin cooked using low-temperature, vacuum-sealed cooking. The study included marinades based on pineapple juice, red wine, kefir and a mixture of dried herbs. The assessment of the effect of marinades was based on the analysis of the color, texture, chemical composition and organoleptic properties of the meat after cooking using the sous vide method. In the experimental part, instrumental determinations of color and texture, analysis of the chemical composition and sensory assessment of the meat were carried out. Marinating for 12 h in red wine and dry marinating causes darkening of the meat. The hardness of meat marinated after 2 h increased compared to the control group; similar relationships were observed for gumminess and chewiness. However, after 12 h of marinating, the hardness of cycle 1 and hardness of cycle 2, as well as chewiness and gumminess, were significantly reduced below the level of the characteristics for the control group, except for the meat marinated in wine. Meat marinated in red wine and using the dry method received higher scores, while longer marinating resulted in more favorable scores.